Differences between the oral changes presented by patients with solid and hematologic tumors during the chemotherapeutic treatment - Isabella Lima Arrais Ribeiro; Sâmara Munique Silva; Rebecca Rhuanny Tolentino Limeira; Paulo Rogério Ferreti Bonan; Ana Maria Gondim Valença; Eufrásio Andrade de Lima Neto; Ricardo Dias de Castro (University of São Paulo, 2019)
Abstract Objective: This study sought to identify the differences between the oral changes presented by patients with solid and hematologic tumors during chemotherapeutic treatment. Methodology: This is an observational, prospective and quantitative study using direct documentation by follow-up of 105 patients from 0 to 18 years using the modified Oral Assessment Guide (OAG). Of the 105 patients analyzed, 57 (54.3%) were boys with 7.3 years (±5.2) mean age. Hematologic neoplasms accounted for 51.4% of all cases. Results: Voice, lips, tongue, and saliva changes were not significantly different (p>0.05) between patients with solid or hematologic tumors and during the follow-up. From the 6th until the 10th week of chemotherapeutic treatment alterations in swallowing function, in the mucous membrane (buccal mucosa and palate), in the labial mucosa, and in the gingiva occurred and were distributed differently between the two tumors groups (p<0.05). The main alterations were observed in patients with hematologic tumors. Conclusion: It was concluded that the oral changes during the chemotherapeutic treatment occurred especially in swallowing function, in the mucous membrane, in the labial mucosa and in the gingiva, and these alterations were found mainly in patients with hematologic tumors.